Identification of risk factors and development of detection algorithm for denosumab‐induced hypocalcaemia. (24th August 2018) - Imatoh, Takuya; Sai, Kimie; Takeyama, Mayu; Hori, Katsuhito; Karayama, Masato; Furuhashi, Kazuki; Segawa, Katsunori; Kimura, Michio; Kawakami, Junichi; Saito, Yoshiro
Summary: What is known and objective: This study used electronic medical records to identify risk factors and establish a detection algorithm for denosumab‐induced hypocalcaemia. Methods: We identified 201 patients with cancer who were initially prescribed denosumab. Hypocalcaemia was defined as an adjusted serum calcium level of ≤2.13 mmol/L. A diagnosis of denosumab‐induced hypocalcaemia was confirmed by two physicians after reviewing patient medical records. We evaluated patient characteristics as potential screening factors. Moreover, a retrospective cohort study was conducted to identify risk factors for denosumab‐induced hypocalcaemia. Odds ratios (ORs) were estimated using logistic regression analysis. Results: We analysed 164 patients with a low risk of hypocalcaemia. Among these, 29 (17.7%) patients were suspected to have denosumab‐induced hypocalcaemia. The times to onset of definitive hypocalcaemia were shorter among these patients than among patients with non‐denosumab‐induced hypocalcaemia. Based on receiver operating characteristic curve analysis, we used time to onset of hypocalcaemia of ≤90 days as a second screening factor. The positive predictive value of this factor was 87.5%. In the retrospective cohort study, a significant difference was observed among patients with serum alkaline phosphatase (ALP) levels of >5.95 μkat/L before initial prescription ( P  <   0.01). Patients with higher serum ALP levels had a 6.63 times higher risk of developing hypocalcaemia than those without increased serum ALP levels (OR: 6.63, 95% confidence interval [CI]: 1.79‐29.31). The same results were observed in a sensitivity analysis using another database. What is new and conclusion: We developed a detection algorithm for denosumab‐induced hypocalcaemia based on calcium levels and time to onset of hypocalcaemia. We also identified elevated ALP levels as a risk factor for hypocalcaemia. Clinicians should carefully monitor initial serum calcium levels and screen for signs of hypocalcaemia in patients receiving denosumab who demonstrate elevated serum ALP levels. Abstract : The novel algorithm for denosumab‐induced hypocalcaemia based on calcium levels and time to onset of hypocalcaemia ( <90 days) was superior to an algorithm based only on serum calcium levels. Moreover, this study suggested that an elevated total serum ALP level was a risk factor for denosumab‐induced hypocalcaemia in patients prescribed denosumab.